Exploring the Level of Speaking Performance Among EFL Students - Fauzan, Muhammad Miftah; Fitrah, Atiyah Inayah; Korompot, Chairil Anwar; Sakkir, Geminastiti (Universitas Negeri Makassar, 2024)
Abstract. This study explores the level of speaking performance among English as a Foreign Language (EFL) students, focusing on their ability to deliver short presentations in English. The study employs short presentations as the primary instrument for evaluating speaking skills, with an assessment rubric used to measure key criteria such as fluency, pronunciation, vocabulary, comprehension and grammar. The sample of the study consists of twenty-eight EFL students from the English Language Education study program, at Universitas Negeri Makassar using cluster random sampling. The data were analyzed using SPSS 25 to determine the frequency and percentage distributions to identify common patterns in speaking performance levels. Additionally, the mean score is calculated to provide a quantitative measure of the overall speaking performance across the respondents. The findings of the data analysis revealed that the level of EFL students’ speaking performance represents B- level with a mean score of 74.46. As a result, the study emphasizes the importance of structured assessment tools like rubrics in providing objective and comprehensive evaluations of students' speaking performance, and suggests that targeted instructional strategies could help improve specific areas of speaking proficiency. Keywords: Explore, Speaking Performance, Speaking Level, Students